Children's Digital Rights: An In-depth Analysis of Indonesia, Europe, and the US - Tahir, Ridwan; Lestari, Titie Yustisia (Eduvest - Journal of Universal Studies, 2025)
The protection of children's digital privacy has become an increasingly critical issue in the modern digital age, as children are more connected to the internet than ever before. This study conducts a comparative analysis of child privacy protection frameworks in Indonesia, Europe, and the United States, focusing on legislative approaches, enforcement mechanisms, and parental in-volvement. While the General Data Protection Regulation (GDPR) in Europe provides a com-prehensive and flexible framework, the Children’s Online Privacy Protection Act (COPPA) in the United States takes a more targeted approach, focusing on children under 13. Indonesia’s Per-sonal Data Protection Law (PDP Law), still in development, offers potential but lacks specific child-focused provisions. Key findings highlight the strengths and weaknesses of these frame-works, particularly in age thresholds for consent, parental involvement mechanisms, and penal-ties for violations. This study underscores the need for Indonesia to harmonize its legal frame-work with international best practices by incorporating child-specific protections, fostering digital literacy, and strengthening enforcement mechanisms. By leveraging lessons from global stand-ards, Indonesia can ensure a safer and more empowering digital environment for its younger generation. The research provides actionable insights for policymakers, educators, and technol-ogy providers to collaboratively address the complexities of safeguarding children’s digital privacy.